Relationship among Workplace Spirituality, Work Engagement and Grit - Setiabudhi Setiabudhi; Prakrisno Satrio; Rammansyah Hidayat; Eva Nur Rachmah; Fahyuni Baharudin (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Workplace Spirituality is an emerging concept of occupational health and positive psychology that realizes that employee’s inner life at workplace in context with the community is nurtured by meaningful work. It is known to enhance work performance by nourishing the spirit of employees at work. The present study aimed to investigate the relationship among workplace spirituality, work engagement and grit. The authors collected data from 275 full-time employees in Kabupaten Pamekasan using convenient sampling. The relationship among workplace spirituality, work engagement and grit was measured using correlation and the influence of demographic variables (age, tenure and educational qualification) on workplace spirituality, work engagement and grit was measured using ANOVA. Results showed significant positive correlation between meaning at work and work engagement (r = .359, p<0.05). ANOVA findings indicate that age, tenure and educational qualification significantly differed across workplace spirituality, work engagement and grit.